Composition containing bifidobacterium lactis and breast milk oligosaccharide and application thereof - LIU BIAO; SITU WENYOU; WANG WENDAN; GU FANGJIE; WISE GISELA ADRIANA; SCHMIDT, GARRETT; VAN LUU-BAUMANN CAROLINE ANNIKA (2022)
The invention provides a composition containing bifidobacterium lactis and breast milk oligosaccharides and application of the composition, and the composition is a composition containing the bifidobacterium lactis and the breast milk oligosaccharides (HMOs for short), and the composition is a composition containing the bifidobacterium lactis and the breast milk oligosaccharides (HMOs for short). The composition can effectively improve the resistance of organisms to staphylococcus aureus infection, can improve the innate immunity and/or aging resistance of the organisms, and can be added into various healthy foods and health foods. 本发明提供了一种含乳双歧杆菌与母乳低聚糖的组合物及其应用，所述组合物是一种包含乳双歧杆菌(Bifidobacterium lactis)与母乳低聚糖(Human Milk Oligosaccharides，简称HMOs)的组合物。该组合物可有效提升生物体对金黄色葡萄球菌感染的抵御能力、可提高生物体先天免疫和/或抗衰老，可添加在各种健康食品以及保健食品中。